2015
DOI: 10.1097/prs.0000000000001454
|View full text |Cite
|
Sign up to set email alerts
|

Objective Clinical Assessment of Posture Patterns after Implant Breast Augmentation

Abstract: Background:An increased weight of the breasts causes several spinal postural alterations that reduce the ability to perform dynamic tasks requiring a stable balance. The effects of the increased weight of the breasts on static posture after implant breast augmentation have not been investigated yet.Methods:Forty volunteer healthy women were asked to wear different sized breast implants (800, 400, and 300 g) inside a dedicated sports bra for 6½ consecutive hours during their everyday life activities, 1 day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…3 The change in body posture after mastectomy due to the weight differences after losing a breast has also been investigated by several groups. 19 Bak et al 20 showed a change in body posture in women after mastectomy as compared with healthy women; however, they did not find any significant correlation between the mastectomy side and the direction of asymmetry in body posture.…”
Section: Savaş Serel Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…3 The change in body posture after mastectomy due to the weight differences after losing a breast has also been investigated by several groups. 19 Bak et al 20 showed a change in body posture in women after mastectomy as compared with healthy women; however, they did not find any significant correlation between the mastectomy side and the direction of asymmetry in body posture.…”
Section: Savaş Serel Et Almentioning
confidence: 99%
“…3 The weight of breasts has an effect on the center of gravity of women, causing a change in body posture. 1,[3][4][5][6][7][8] One of the expected outcomes of mastectomy, therefore, is long-term postural changes. There are, indeed, several studies in the literature proving the change in body posture in women after mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…An extremely large breast size may lead to difficulties in daily life and studies have demonstrated that physical weight and psychological factors may cause an altered skeletal posture (1)(2)(3). Moreover, many studies have reported that having both breasts is important in maintaining a center of gravity and stable posture (4)(5)(6). In the treatment of unilateral breast cancer, oncological safety is the primary goal; however, breast reconstruction surgery to esthetically resemble the natural look of the contralateral healthy breast is also essential.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, our observations and previous findings highlight the need for the awareness of potential risks involved when one's center of gravity is disrupted, particularly for those with an existing spinal abnormality. One recent study found that wearing a breast implant inside a dedicated sports bra can induce reversible changes in spinal curvature 13 …”
Section: Discussionmentioning
confidence: 99%